Cover Picture: Nanoscale Control of Homoepitaxial Growth on a Two‐Dimensional Zeolite (Angew. Chem. Int. Ed. 2/2017). Issue 2 (3rd January 2017) - Shete, Meera; Kumar, Manjesh; Kim, Donghun; Rangnekar, Neel; Xu, Dandan; Topuz, Berna; Agrawal, Kumar Varoon; Karapetrova, Evguenia; Stottrup, Benjamin; Al‐Thabaiti, Shaeel; Basahel, Sulaiman; Narasimharao, Katabathini; et al.
Abstract : Akin to colors on an artist′s palette that enable them to paint the landscape according to their imagination; scientists are constantly seeking methods to manipulate nanoscale crystal features as they will. In their Communication onpage 539 ff., D. Kim, J. D. Rimer, M. Tsapatsis, and co‐workers report on epitaxial solution‐based growth conditions enabling them to tailor 2D zeolite thin films and hierarchical catalysts at a scale that approaches single‐unit‐cell dimensions.